The Effects Of Migration On Income, Health, And Education: A Data Analysis Of Indonesia National Social Economic Survey 2018 - Tri Budiono; Nugroho Bintoro (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2022)
This research is aim to get a better understanding of the impact of migration on the welfare of migrants in Indonesia. Using Instrumental Variable 2sls (IV) and IV probit, this study finds that migration has a positive effect on income. Nevertheless, it was discovered that migration increases the likelihood of children being unhealthy and that it causes schooling to be interrupted when they should be in high school. migration's potential detrimental influence on health and education should be anticipated by policymakers.